English Conversation Videos: A Study of Their Impact on English Language Education Students’ Academic Listening Skills and Attitudes - Muhammad Arbain (Lembaga Pengembangan Kinerja Dosen, 2025)
This study explores the impact of English conversation videos on the academic listening skills and attitudes of English Language Education (ELE) students. As technology reshapes language education, video-based materials, especially conversation videos, provide authentic language exposure, enhancing comprehension and pragmatic skills. Using a pre-experimental design with pretest-posttest assessments and a Likert-scale questionnaire, the study involved 30 second-year ELE students at the Islamic University of Kalimantan Muhammad Arsyad Al-Banjari. Results showed a significant improvement in listening skills, with posttest scores rising from a mean of 81.67 to 87.17 (t(29) = 11.36, p < 0.001). Students had positive attitudes towards using videos, noting high motivation and relevance to their future careers. However, while videos helped with comprehension and accent recognition, they were less effective in reducing anxiety or improving test performance. These findings underscore the value of conversation videos in academic listening development and suggest areas for future research on their impact on higher-level listening skills and anxiety management.